Practical equality : forging justice in a divided nation - Tsai, Robert L., 1971- (New York : W. W. Norton & Company, 2020)
The American University law professor offers a guide for activists, lawyers, public officials, and citizens that identifies innovative use of American legal ideas to pursue equality and promote fairness, justice, and free speech.
Practical equality -- Fair play -- The rule of reason -- No cruelty -- Free speech.
Reprint. Originally published: 2019.
Includes bibliographical references and index.
Keywords: Equality before the law -- United States -- History; Equality -- United States -- History; Freedom of speech -- United States -- History; Justice, Administration of -- United States -- History; Equality before the law -- United States